Reducing the water quenching processes using heavy water in capillary electrophoresis with fluorescence detection - Mádi, Lenka; Kučera, Josef; Káňa, Štěpán; Bržezická, Taťána; Táborský, Petr (Journal of chromatography. A, 2024)
Water, ubiquitous in analytical methods, is renowned for its fluorescence quenching properties, influencing techniques like fluorescence spectrophotometry or techniques with fluorescence detection. This study explores the impact of water (H₂O) substitution for heavy water (D₂O) on the fluorescence behavior of anthraquinones and anthracyclines. Anthraquinones and anthracyclines play crucial roles in pharmacy, serving as essential components in various therapeutic formulations, particularly in cancer treatment and other pharmacological interventions. Capillary electrophoresis (CE) with heavy water as the background electrolyte (BGE) solvent offers superior sensitivity to the separation and detection of these analytes. Experimental results demonstrate the improved detection limits and separation efficiency of selected anthraquinones rhein (RH), aloe-emodin (AE), and anthracyclines doxorubicin (DOX), epirubicin (EPI) and daunorubicine (DAU) in heavy water-based buffers, highlighting the potential of heavy water in advancing analytical chemistry.
Keywords: antracykliny; Fluorescence detection; anthrachinony; voda; Limit of Detection; Capillary electrophoresis; Water; limita detekce; oxid deuteria; Electrophoresis, Capillary; Spectrometry, Fluorescence; Anthraquinones; Anthracyclines; Deuterium Oxide; Heavy water; elektroforéza kapilární; fluorescenční spektrometrie